ANALISIS RISIKO KESEHATAN LINGKUNGAN (ARKL) PAJANAN BESI (Fe) PADA DEPOT AIR DI KELURAHAN DWIKORA KECAMATAN HELVETIA - Amirah, Nada; Zahara, Eirin; Harahap, Nurul Dahlia (Jurnal Penelitian Kesmasy, 2025)
Drinking water is a fundamental necessity for human life. Safe drinking water should be clear, colorless, and free from odor. The presence of heavy metals such as iron (Fe) in refillable drinking water can occur due to contaminated raw water sources or inadequate water treatment processes at refill water depots (DAMIU). Based on the Decree of the Minister of Health No. 492 of 2010, the maximum permissible concentration of iron (Fe) in drinking water is 0.3 mg/L. This study employed a descriptive quantitative method using the Environmental Health Risk Analysis (EHRA) approach to evaluate the potential health risks associated with iron (Fe) exposure in drinking water depots located in Dwikora Village. Measurements of Fe concentrations from four water samples were compared with the maximum permissible standard stated in Permenkes No. 492 of 2010 and analyzed using the EHRA framework. The research population consisted of housewives who consumed water from DAMIU in Dwikora. Data were collected through questionnaires and interviews. The findings revealed that the concentration of iron (Fe) in all four water samples remained below the permissible limit of 0.3 mg/L. This suggests that the Risk Quotient (RQ) values for Fe exposure in all samples were below 1, indicating that the drinking water from the DAMIU in Dwikora is still safe for public consumption.